Bottom-up assembly of multicomponent coordination-based oligomers - Mondal, Prakash Chandra; Jeyachandran, Yekkoni Lakshmanan; Hamoudi, Hicham; Zharnikov, Michael; Gupta, Tarkeshwar (The journal of physical chemistry. C, Energy, materials, and catalysis, 2011)
Transition metal complexes allow a high degree of molecular design flexibility through symmetry considerations and ligand architecture, which can be explored for the fabrication of ordered multilayer assemblies through bottom-up approach. Here we describe the preparation of such assemblies, viz. multicomponent coordination-based oligomer films on siloxane-based templates by wet-chemical layer-by-layer deposition process. In these films we combined optically rich iron and ruthenium polypyridyl complexes having pendant pyridine groups (so-called metallo-ligands) and a coinage metal (copper or silver) that acted as a linker between the polypyridyl complex moieties. The properties and structural parameters of the primary template and the oligomer films were studied by X-ray photoelectron spectroscopy, near-edge X-ray absorption fine structure spectroscopy, UV-vis spectroscopy, spectroscopic ellipsometry, atomic force microscopy, and contact angle goniometry. A linear increase in the film thickness upon addition of every next layer suggests that the long-range order of the system is determined by the octahedral structure of the metallo-ligand and square-pyramidal/tetrahedral geometry of the coinage metal linker. Spectroscopic data indicate the existence of electronic communication throughout the individual metallo-organic chains.
Gesehen am 07.09.2022